Bone Bruise versus Fracture on MRI and the Relevance to Return to Play - Belair, Jeffrey A.; Zoga, Adam C. (Seminars in Musculoskeletal Radiology, 2024)
We review the spectrum of acute osseous injuries in athletes, ranging from osseous contusion (bone bruise) injuries to nondisplaced cortical fractures. The basic biomechanical concepts, underlying histopathologic changes, and characteristic magnetic resonance imaging (MRI) features of acute osseous injuries are presented. Bone bruise injuries of varying severity are highlighted to showcase the breadth of imaging findings on MRI and methods for characterizing such lesions. We emphasize the importance of accurately assessing patterns of injury on MRI to communicate more effectively with team medical staff and recognize the implications on return to play. This article offers the foundational tools for approaching bone bruise injuries in elite athletes to add value to the diagnosis and treatment of this unique patient population.
Keywords: bone bruise; osseous contusion; fracture; sports; return to play